HUBUNGAN FAKTOR DEMOGRAFI, AKTIVITAS FISIK, RIWAYAT PENYAKIT, DAN METODE KB DENGAN KELUHAN PERIMENOPAUSE PADA PEDAGANG SERABI AMBARAWA, SEMARANG - Celline Oktiani; Dharminto Dharminto; Farid Agusyahbana; Atik Mawarni (Jurnal Kesehatan Masyarakat (Undip), 2017)
In 2016 in Indonesia has reached 14 million menopausal women, or 7.4% of the total population. Increased life expectancy causes the number of menopausal women will increase. Ambarawa merchants with an age range entering menopausal age and selling places in pollution prone areas. Where mentioned women who are often exposed to vehicle fumes and inhaling the polluted air can cause the ovum to become unable to function properly. As a result there are various menopause gripes that will decrease the quality of life of a menopausal woman. The purpose of this research was to analyze the relation of demography factor, physical activity, disease history, and kb method with perimenopause gripes on Ambarawa serabi merchants, Semarang. The type of research used is Explanatory Research with Cross Sectional approach. The population in this research is all 40 serabi merchants aged 40-55 years is 41 people who then taken entirely as research respondents. The highest percentage was 65.9% of respondents aged ≥ 50 years, marital status 78.0% had husbands, 46.3% had primary school education, 83.3% had high physical activity, 65.9% had no history of disease, and 68, 3% had used hormonal contraceptive for ≥ 3 months in a row. Based on statistical test Chi Square shows there is relationship of physical activity with perimenopause gripe (p = 0,015). Unrelated variables are demography factor, disease history, and family planning method. Based on logistic regression test with enter method showed that there was influence of physical activity with perimenopausal gripe on Ambarawa serabi merchants, Semarang (p = 0,030: OR = 20,312; CI = 1,348-306,110). Suggestions for further researchers is to examine by reviewing of various factors / other variables that have not been disclosed in this study. For serabi merchants to increase physical activity such as exercise in order to reduce perimenopause gripes..